METHODOLOGICAL ASPECTS OF DEVELOPING HERMENEUTIC COMPETENCE OF FUTURE MUSIC TEACHERS (Scientific journal of the Fergana State University, 2026)
The article examines the theoretical and methodological foundations for developing the hermeneutic competence of future music teachers. It explores effective strategies and approaches for fostering this competence and evaluates the outcomes of its implementation. The study emphasizes the current necessity and pedagogical relevance of hermeneutic competence in teacher education, outlines priority tasks for preparing future teachers in this area, and presents practical insights into interdisciplinary integration within music pedagogy.